Legal Responsibility Of A Notary For Forgery Of The Debtor's Personal Identity In The Deed Of The Credit Agreement In The Bank - Parmono, Budi; Sunardi, Sunardi; Kholifah, Siti (Universitas Islam Malang, 2024)
Abstract: The importance of credit agreements being made authentically is as a legal guarantee of strong and legal evidence for the parties entering into the agreement. In making a deed, the Notary must adjust the evidence provided by the person present with other evidence, however, in making the deed, a notary must be thorough and careful so that there is no forgery in making the deed. The formulation of the problem is as follows: What is the responsibility of the notary in the event that the debtor's identity is proven to be falsified in the credit agreement deed at the Bank and what are the legal consequences for the credit agreement deed in the event that the debtor's identity is proven to be falsified. This research is nurmative research with a statutory approach, and a Conceptual Approach and a legal dictionary approach. Results of research on the responsibility of notaries regarding proven falsification of debtors' personal identities in credit agreement deeds at banks. a) If the notary is aware of falsification of identity or participates in it, the responsibility of the notary in the case of proven falsification of the debtor's identity in the credit agreement deed at the bank is that the notary must be held responsible both civilly if there is a loss, and criminally if the notary already knows that there is a falsification of identity. the parties, in addition to administrative sanctions and the notary's code of ethics as regulated in UUJN article 7 paragraph 2. b) If the notary is not aware of the existence of forged documents. And if the falsification was carried out by the parties, the parties must be held absolutely responsible, both civil and criminal, and responsible for their own mistakes. Legal Consequences of a Deed of Credit Agreement Proven to be a Falsification of the Debtor's Personal Identity. If the underlying agreement does not fulfill the legal requirements for an agreement as regulated in Article 1320 and Article 1868 of the Civil Code, it will have legal consequences, including: a) Degradation (loss of perfect evidentiary power) or the deed becoming under the control of hands. b) Nullity by law. This means that if the objective requirements are not met then the agreement is null and void by law. c) Can be cancelled. This means that if the agreement does not meet the subjective requirements, the agreement can be canceledKey words: responsibility, forgery, notary/parties